2018
DOI: 10.1101/321182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of social representation in the mouse prefrontal cortex

Abstract: The prefrontal cortex (PFC) plays an important role in regulating social functions in mammals, and impairments in this region have been linked with social dysfunction in psychiatric disorders. Yet little is known of how the PFC encodes social information and of how social representations may be altered in such disorders. Here, we show that neurons in the medial PFC (mPFC) of freely behaving mice preferentially respond to socially-relevant sensory cues. Population activity patterns in the mPFC differed consider… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 84 publications
3
10
1
Order By: Relevance
“…We propose that this is the cause of the social deficit of RTT mice because recovering the capacity for prelimbic pattern decorrelation rescues their social deficit, despite the fact that MeCP2 deficiency affects the whole brain of this mouse model. Our result echoes a recent study using a mouse model of another autism-associated neurodevelopmental disorder showing that both the categorization of sensory stimuli and the refinement of social representations (provided by odor) were impaired in the mPFC circuit of mice lacking the autism-associated gene Cntnap2 13 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We propose that this is the cause of the social deficit of RTT mice because recovering the capacity for prelimbic pattern decorrelation rescues their social deficit, despite the fact that MeCP2 deficiency affects the whole brain of this mouse model. Our result echoes a recent study using a mouse model of another autism-associated neurodevelopmental disorder showing that both the categorization of sensory stimuli and the refinement of social representations (provided by odor) were impaired in the mPFC circuit of mice lacking the autism-associated gene Cntnap2 13 .…”
Section: Discussionsupporting
confidence: 87%
“…Animal studies showed that neural activity in the prelimbic cortex, part of the mouse medial PFC (mPFC), carries both spatial and social information , the combination of which underlies the murine tendency to return to locations where they have previously interacted with a conspecific 7 . When a mouse approaches or interacts with a fellow mouse 6,11,12 , or senses the odor of social cues 13 , mPFC neurons become more active, but it is unclear how this activity encodes different stimuli to guide social discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an opsin-mediated increase in PV + cell excitability or a decrease in pyramidal neuron activity within the prelimbic mPFC can rescue social behavior and hyperactivity in Cntnap2 KO mice (Selimbeyoglu et al, 2017). Such disruptions in E/I balance could also reflect as broader-scale alterations in oscillatory power and synchrony and could be mechanistically linked to the altered representation of social stimuli in the mPFC of Cntnap2 KO mice (Levy et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Such disruptions in excitatory/inhibitory balance could also be reflected in broader scale as alterations in oscillatory power and synchrony. Moreover, these synaptic alterations could be mechanistically linked to the altered representation of social stimuli in the mPFC of Cntnap2 KO mice 63 . Consistent with this notion, a number of syndromic forms of autism show disrupted oscillations, such as Angelman Syndrome, which presents with enhanced delta oscillations 58 , and Duplication 15q Syndrome, which shows enhanced beta oscillations 64 .…”
Section: Discussionmentioning
confidence: 99%